Blockchain-Enabled Intelligent Platforms: Enhancing Trust and Transparency in Halal Food - Kiki Hardiansyah Siregar; Tasriani Tasriani (Journal of Intelligent Systems and Information Technology, 2026)
Indonesia's halal industry faces significant challenges in bridging the gap between 30 million products requiring mandatory halal certification and only 9.6–9.8 million products officially registered with BPJPH, compounded by 40% consumer skepticism toward halal claims due to a paper-based certification system vulnerable to forgery. Blockchain-enabled intelligent platforms are essential to enhance transparency and trust through real-time digital verification. To design and test a blockchain-based halal verification platform integrated with QR codes and intelligent information systems, enabling end-to-end tracking from producers to consumers, reducing certification fraud, and improving consumer trust and system efficiency. This study employs a quantitative-explanatory R&D approach to develop a three-tier system (frontend web/mobile, Python/SQL backend, blockchain simulation), tested for performance on 10,000–100,000 halal product datasets. Primary data (Likert-scale trust scores, response time, accuracy) and secondary data (BPJPH statistics) were analyzed using descriptive statistics and scalability simulations. Research Findings: The platform achieved 99.7% verification accuracy, 1.2–2.1 second response times, and a 0.3% error rate. Consumer trust scores improved from 3.1 to 4.3 (+39%), with 92% of users rating the system as "very user-friendly." The system scaled effectively to 100,000 datasets with CPU usage below 40%. Blockchain-enabled intelligent platforms effectively enhance consumer trust, certification transparency, and computational efficiency, supporting Indonesia's target of 100% mandatory halal certification by 2030–2035. This platform is ready for integration with BPJPH's ecosystem for national-scale UMKM and halal industries.